Aspirin Resistance as a Result of Impaired Interaction of Platelets and Neutrophils in Patients with Coronary Heart Disease - M. D. Goncharov; A. A. Savchenko; Yu. I. Grinshtein; I. I. Gvozdev; A. A. Kosinova; T. S. Mongush (Рациональная фармакотерапия в кардиологии)
Aim. To study the relationship between the levels of synthesis of reactive oxygen species (ROS) by platelets and neutrophils in patients with coronary heart disease (CHD) before and after coronary artery bypass grafting (CABG), depending on sensitivity to acetylsalicylic acid (ASA).Material and methods. The study included 95 patients with coronary artery disease who are indicated for CABG surgery. The control group consisted of 30 healthy donors. The antiplatelet therapy was stopped for at least 5 days before CABG. In the postoperative period, from the first day, all patients were received 100 mg of an enteric form of acetylsalicylic acid (ASA). Resistance to ASA was determined at the level of platelet aggregation with arachidonic acid ≥20% by optical agregometry at least at one observation point: before CABG, on 1-3 day and on 8-10 day after surgery. We evaluated the spontaneous and induced lucigenin-dependent chemiluminescence (CL) of platelets (ADP induction) and neutrophils (zymosan induction) by the exit time to maximum intensity (Tmax), maximum intensity (Imax) and area (S) under the CL curve.Results. 70.5% sensitive (sASA) and 29.5% resistant (rASA) to ASA patients were revealed. Prior to CABG, in sASA patients, the Imax of spontaneous and zymosan-induced neutrophil CL and CL platelet activity was increased relative to control values. Tmax of spontaneous platelet CL, Imax and S under the ADP-induced platelet CL curve were lower in sASA patients, if to compare with rASA patients. On the 1st and 8-10th day after CABG in sASA patients, the CL indicators of neutrophil and platelet activity also remained elevated compared to control values. On the 1st day after CABG decreased levels of S under the spontaneous CL curve of neutrophils in rASA patients was established compared with sASA patients, and increased levels of Imax and S under the curve of induced neutrophil CL were detected in comparison with the control range. In rASA patients, the values of Tmax of spontaneous platelet CL decreased in relation to the values detected in the control group and sASA patients. On the 8–10th day after CABG, most indicators of spontaneous and zymosan-induced CL neutrophils in rASA patients were also increased compared to control values. In rASA patients a positive correlation of Imax-induced CL was found (r=0.83) on the 1st day after CABG and negative correlations of Tmax of spontaneous CL (r=- 0.75) and S under the curve induced CL (r=-0.70) on the 8-10th day were detected between platelets and neutrophils.Conclusion. In sASA patients with coronary heart disease before and after CABG, a high level of synthesis of superoxide radical by neutrophils and platelets was detected. The relationship between the levels of the synthesis of superoxide radical by neutrophils and platelets was found only after CABG in rASA patients. Increased synthesis of superoxide radical due to metabolic and regulatory relationships in neutrophils and platelets stimulates pro-inflammatory processes in coronary artery disease and determines the sensitivity of platelets to ASA.